Annotated bird sighting list for fall 1999 compiled by Jim Sinclair - Sinclair, Jimet al (1999)
An annotated list of birds sighted by Jim Sinclair. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed